Delayed rupture of the descending thoracic aorta caused by penetrating intrathoracic injury from multiple rib fractures: Penetrantna poškodba torakalne aorte zaradi serijskega zloma reber - Flis, Vojko; Antonič, Jože; Borovšak, Zvonko; Glumbić, Ivana; Kobilica, Nina (Acta Medico-Biotechnica, 2021)
Purpose: Thoracic trauma comprises 10-15% of all traumas. Blunt chest trauma is a major cause of morbidity and mortality, especially in the presence of flail chest. Chest-wall instability may be treated conservatively with analgesia, assisted ventilation and clearing of bronchial secretions. However, such treatment does not prevent additional injuries from broken ribs. It was thought that penetrating intrathoracic aortic injury after rib fractures was rare, but with emerging new cases the question of surgical stabilization of flail chest is reopened.Case report: We describe a patient with flail chest injury on both sides who incurred a significant rib penetrating injury to the aorta days after the initial trauma. The thoracic surgeon did not decide on surgical fixation of the chest wall. Because of the flail chest, he remained intubated and mechanically ventilated. The patient was admitted to the ICU (Intensive Care Unit). The patient died after failed cardiac resuscitation during transportation to the operating room.Conclusion: Although surgical fixation of flail chest segments can have potential advantages, there is no commonly accepted and safe procedure for fracture fixation of posterior rib fractures. A specific rib plate for posterior rib fractures that takes into account the structural properties and fixation constraints of ribs to reduce the prevalence of complications has yet to be constructed.
Keywords: blunt thoracic trauma; rib fractures; penetrant injury to aorta